2017
DOI: 10.1590/0102-311x00139115
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes por quedas, cortes e queimaduras em crianças de 0-4 anos: coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 2004

Abstract: Knowledge on the incidence of childhood accidents according to the child's stage of development is important for designing preventive programs targeting each age bracket. The aim of this study was to describe the incidence of falls, cuts, and burns in children up to four years of age according to family economic status and maternal age and schooling, in children from the 2004 Pelotas (Brazil) birth cohort. We calculated the incidence rates and incidence rates ratios for the 0-12, 12-24, and 24-48-months

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
15

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
0
9
0
15
Order By: Relevance
“…At each level, the P value of the variables was verified, and those with P value<0.20 remained in the final model to control for possible confounding effect. Based on the literature, which is consistent in indicating higher incidences of injuries among boys, all analyses were planned to be stratified according to the child’s sex 3 5 18. Complementary analyses were run to assess the relationship between maternal depression and each of the types of injuries investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each level, the P value of the variables was verified, and those with P value<0.20 remained in the final model to control for possible confounding effect. Based on the literature, which is consistent in indicating higher incidences of injuries among boys, all analyses were planned to be stratified according to the child’s sex 3 5 18. Complementary analyses were run to assess the relationship between maternal depression and each of the types of injuries investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Childhood injuries are often interpreted as a work of chance, but most often predisposing factors play a role on its occurrence. A population-based study, conducted in the municipality of Pelotas, RS, Brazil, showed that the prevalence of falls, cuts and burns ranged from 5.2% for burns during the first year of life, among girls, to 77.7% for falls during the second year of life, among boys 3. In this same study, maternal factors such as younger age (<18 years), lower socioeconomic status and lower educational level were associated with higher incidence of injuries among children aged 0–4 years 3…”
Section: Introductionmentioning
confidence: 99%
“…The global burden of disease estimates indicate that 172 million falls result in short-or long-term disability annually [27] . A cohort study in Brazil found that falls were the most commonly reported injuries in all age groups among children [28] . Falls among children and adolescents in Zhuhai City were the main reason for hospitalization and outpatient/emergency department visits.…”
Section: Discussionmentioning
confidence: 99%
“…Estes eventos têm ocupado lugar de destaque entre as causas de morbimortalidade infantil e por isso são considerados problema de saúde pública em todo o mundo. Contudo, os dados disponíveis representam apenas minudência dos acidentes, pois muitos nem chegam a ser atendidos por serviços de saúde e pessoas presentes no momento do evento realizam os primeiros socorros (2)(3)(4) .…”
Section: Introductionunclassified